(untitled) (Texas Journal of Medical Science, 2026)
Arterial hypertension has become an increasingly prevalent health concern among young people worldwide. This study examines the growing incidence of hypertension in youth, its etiological factors, pathophysiological mechanisms, and preventive strategies. Major risk factors include unhealthy dietary habits, sedentary lifestyle, chronic stress, obesity, hereditary predisposition, and excessive consumption of energy drinks. The article highlights the importance of early diagnosis, regular blood pressure monitoring, and implementation of preventive interventions such as healthy nutrition, physical activity, stress management, and sleep hygiene. Effective prevention and early management of hypertension in young populations may significantly reduce future cardiovascular morbidity and mortality